2012
DOI: 10.1017/s1479262112000275
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gaps in pearl millet germplasm from East and Southern Africa conserved at the ICRISAT genebank

Abstract: Kwe Kwe in Midlands of Zimbabwe were identified as gaps common to geographic area and diversity for some or the other traits. For a successful germplasm collection mission to fill the gaps identified, planning should be made in advance in collaboration and consultation with NARS, local government officials and extension officers. It is suggested to collect the complete passport data including georeference information while collecting the germplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Knowledge of the geographical distribution of economically important traits and the diversity is essential for proper understanding and exploitation of genetic resources. In the present study, the frequency distribution of landraces originating in various countries indicated unequal adaptation of pearl millet across the countries, probably due to natural and human selection as well as the photoperiod and temperature response of landraces (Upadhyaya et al 2012a). Landraces from primary center of diversity for pearl millet covering mostly the West and Central African (WCA) countries harbor a wide range of climatic and environmental conditions as well as diverse farmer preferences and pearl millet utilization habits, were found as highly variable for days to 50 % flowering, plant height, panicle exsertion, length, thickness and shape, seed shape and color (Harlan 1971;Bhattacharjee et al 2007;Stich et al 2010).…”
Section: Discussionmentioning
confidence: 44%
“…Knowledge of the geographical distribution of economically important traits and the diversity is essential for proper understanding and exploitation of genetic resources. In the present study, the frequency distribution of landraces originating in various countries indicated unequal adaptation of pearl millet across the countries, probably due to natural and human selection as well as the photoperiod and temperature response of landraces (Upadhyaya et al 2012a). Landraces from primary center of diversity for pearl millet covering mostly the West and Central African (WCA) countries harbor a wide range of climatic and environmental conditions as well as diverse farmer preferences and pearl millet utilization habits, were found as highly variable for days to 50 % flowering, plant height, panicle exsertion, length, thickness and shape, seed shape and color (Harlan 1971;Bhattacharjee et al 2007;Stich et al 2010).…”
Section: Discussionmentioning
confidence: 44%
“…We base our framework on the rationale that the distributions of landraces can be predicted using environmental and socioeconomic drivers, and that important conservation gaps can be identified by characterizing the geographic (accessibility and connectivity) and environmental space across which previous collecting has been carried out. Previous studies assessing gaps in landrace collections only used climate drivers and did not explicitly assess gap prediction robustness (Upadhyaya et al, , ; Upadhyaya, Reddy, Irshad Ahmed, Gowda, & Haussmann, ) nor introduce expert inputs to prioritize collecting.…”
Section: Discussionmentioning
confidence: 99%
“…Though the global germplasm collections are large, there are still sizeable gaps in the ex situ collections of many major crops including sorghum (Jones et al, 1997;Maxted et al, 2008;Upadhyaya et al, , 2010Upadhyaya et al, , 2012Upadhyaya et al, , 2014aUpadhyaya et al, , 2015. Generally, the goal of genebanks is to preserve maximum genetic diversity and that is feasible through identification and exploration of gaps in the collections.…”
Section: Discussionmentioning
confidence: 99%